EXPLORING ONLINE COLLABORATIVE WRITING WITH SOCIAL MEDIA - Habib Nur Afif; Muhammad Luthfi Abdillah (INCARE, International Journal of Educational Resources, 2020)
Online interactive learning is an innovative approach intended to create a commitment to creating narrative text writing, comprehension, and creative client ideas. This assessment's inspiration is to evaluate the effect of online interactive learning on student grades and narrative texts' composition. Analysis has been performed at MTs. Miftahul Huda Tuban in the 7th grade. To determine does online collaborative learning through telegram is successful, researchers use a pre-experimental method when the information is measured using a t-test statistical formula. As a result of the exploration, the mean pre-test was 51,3333, and the mean post-test was 84,000. From the pre-test post-test study results, it can be shown that there is an impact on increasing student scores by using online interactive learning methods through telegram.